Kandungan Logam Berat Timbal (Pb) dan Kadmium (Cd) Pada Badan Air dan Ikan di Perairan Teluk Benoa, Bali - Mardani, Ni Putu Suci; Restu, I Wayan; Sari, Alfi Hermawati Waskita (Current Trends in Aquatic Science; Vol 1 No 1 (2018)DO - 10.24843/CTAS.2018.v01.i01.p14, 2018)
Heavy metals going into the aquatic environment will have an impact on the quality of the aquatic environment and affect the life of the biota in it. This study objectives is to determine the content of heavy metals Pb and Cd in water as well as in the Mullet Fish (Mugil cephalus) and Orange Spotted Rabbit Fish (Siganus guttatus) caught in Benoa Bay. The study was conducted from February to April 2018. The results showed that the content of heavy metals Pb and Cd in the water in Benoa Bay had exceeded the quality standards of metals dissolved in water for marine biota listed on Pergub Bali No. 16 of 2016. The value of Pb heavy metals in Mullet Fish and Orange Spotted Rabbit Fish in some samples have exceeded the maximum limit of heavy metal contamination SNI 7387: 2009. Cd heavy metal in Mullet Fish and Orange Spotted Rabbit Fish have exceeded the maximum limit of Cd metal contamination in fish and the processed product of 0.1 mg / Kg. Bioconcentration factor of metal Pb in Mullet Fish is included in the category of low accumulative properties of Pb heavy metals. BCF value of metal Cd in Mullet Fish shows that Mullet Fish has moderate accumulative properties against heavy metal Cd. Orange Spotted Rabbit Fish belongs to low category of accumulative properties against heavy metals Pb and Cd.